2014
DOI: 10.1007/s40544-014-0053-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic effect on the superlubricity of phosphoric acid between ceramic and sapphire

Abstract: Abstract:In this work, a super-low friction coefficient of 0.003 was found between a silicon nitride ball and a sapphire plate lubricated by phosphoric acid solution. The wear mainly occurred in the running-in period and disappeared after superlubricity was achieved. The friction coefficient was effectively reduced from 0.3 to 0.003 at a constant speed of 0.076 m/s, accompanied by a 12-nm-thickness film. The lubrication regime was indicated to change from boundary lubrication in the running-in period to elasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Liquid superlubricity has been proposed for more than 20 years [52−55]. Its mechanism can be summarized as hydration effect [56], chemical reaction layer [57], hydrodynamic effect [58,59], double electric layer interaction which will be more important in superlubricity [60,61], and the combination of multiple effects [62]. Superlubricity lubricants have been developed from pure water [63], brine [64], acids [65] to acid-alcohol system [66,67], alcohol system [68], bioliquids [69], oil-based system [70], and surfactants [71].…”
Section: Liquid Superlubricitymentioning
confidence: 99%
“…Liquid superlubricity has been proposed for more than 20 years [52−55]. Its mechanism can be summarized as hydration effect [56], chemical reaction layer [57], hydrodynamic effect [58,59], double electric layer interaction which will be more important in superlubricity [60,61], and the combination of multiple effects [62]. Superlubricity lubricants have been developed from pure water [63], brine [64], acids [65] to acid-alcohol system [66,67], alcohol system [68], bioliquids [69], oil-based system [70], and surfactants [71].…”
Section: Liquid Superlubricitymentioning
confidence: 99%
“…Phosphoric acid as a lubricant was first found to achieve superlubricity at the Si 3 N 4 /glass interface in 2011 (Li et al, 2011). Thereafter, acid-based lubricants as a new series of lubricants were investigated by the authors in detail at various tribopairs, such as Si 3 N 4 /glass, Si 3 N 4 /SiO 2 , Si 3 N 4 /sapphire, and ruby/sapphire (Deng et al, 2014;. As depicted in Figure 4a, when a Si 3 N 4 ball slides on a glass disc under the lubrication of H 3 PO 4(aq) , the COF decreases from 0.45 to 0.004 after a wearing-in period of 600 s. The wearing-in period is vital to the achievement of superlubricity and can be divided into two stages according to the evolution of the COF with time.…”
Section: Acid-based Aqueous Lubricantsmentioning
confidence: 99%
“…23 Moreover, the sliding of two surfaces with each other results in a hydrodynamic effect in the limited hydrated water layer, which also plays an important role in the lubrication state of the liquid system. 21 The hydrodynamic effect in the contact area signicantly weakens with the decrease in speed. The subdued lubricating lm can barely support the high contact pressure from the upper Si 3 N 4 ball and results in the direct solid-solid contact of tribopair surfaces, thereby failing to achieve superlubricity state.…”
Section: Superlubricity Failure Mechanism Under Low and High Speedsmentioning
confidence: 99%
“…19 Further studies showed that superlubricity mechanism was mainly attributed to the formation of a three-layer water-containing nanolm with hydrogen bond network (hydrated water layer) between two contacting surfaces aer the tribochemical reaction between acid solution and tribopair surfaces during the running-in process. [20][21][22] The special composite lubricating nanolm can effectively separate the tribopair surfaces and provide a hydrated water layer with ultra-low shear strength instead of a direct frictional contact. Meanwhile, the inuences of the types of acid, hydrogen ion concentration and volume of lubricant on the superlubricity behavior of Si 3 N 4 /glass pair have also been studied.…”
Section: Introductionmentioning
confidence: 99%